A robust resource allocation algorithm for packet BIC-UFMC 5G wireless communications - Del Fiorentino, Paolo; Vitiello, Carmine; Lottici, Vincenzo; Giannetti, Filippo; Luise, Marco (2016 24th European Signal Processing Conference (EUSIPCO), 2016)
In this paper, we present a novel resource allocation (RA) algorithm for packet Universal Filtered Multi-Carrier (UFMC) BIC-based communications, the latter being a novel modulation format possibly envisaged to be applied in 5G wireless systems. Assuming the perfect knowledge of the channel and capitalizing on the specific UFMC signal waveform, the proposed RA strategy optimizes the coding rate and bit loading within the overall bandwidth along with the per-subband power distribution. In the presence of a carrier offset and over fading selective channels, the results we obtained are twofold: i) the UFMC format reveals to be more robust than the conventional OFDM scheme; ii) the performance of the UFMC system itself is further boosted by the optimal choice of radio resources evaluated by the proposed RA algorithm.